Lack of response to imatinib mesylate in a patient with accelerated phase myeloproliferative disorder with rearrangement of the platelet-derived growth factor receptor beta-gene - JN Bastie; I Garcia; C Terre; NC Cross; FX Mahon; S Castaigne (Haematologica, 2004)
Imatinib mesylate has been reported to produce positive results in atypical chronic myeloproliferative disorders (CMD) with chromosomal translocations that disrupt the platelet-derived growth factor receptor beta gene (PDGFRB). We used imatinib to treat a 49-year old man with atypical CMD in accelerated phase and the H4 (D10S170)-PDGFRB fusion gene. After 3 months of treatment, we observed grade 4 hematologic toxicity and a lack of response.